Evaluation of two papaya hybrids introduced in Cuba - Alonso, Maruchi (2009)
The aim of this work was to characterized 2 papaya hybrids, “Tainung-01” and “Scarlett Princess”, introduced into the germoplasm bank of the Instituto de Investigaciones en Fruticultura Tropical, La Habana, Cuba. They were compared to the cuban cultivar Maradol. Results confirm that both hybrids show phenotypical characteristics of the Formosa Group, with elongated fruits in hermaphroditic plants. The average fruit weigtht is 1.6 kg ( ̈Tainung-01 ̈) and 1.7 kg ( ̈Scarlett Princess ̈), of orange-reddish and red pulp, respectively, and their productivity between 98.5 and 63.8 kg.plant-1, characteristics that indicate the possibility of using them in genetic improvement programs, as well as directly by growers.